Early detection of parkinson’s disease using image processing and artificial neural network - Rumman, Mosarrat; Tasneem, Abu Nayeem; Farzana, Sadia (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.